Study of the in vitro metabolic profile of a new alpha(2)-adrenergic agonist Cheek for in rat and human liver microsomes by using liquid chromatography-multiple-stage mass spectrometry and nuclear magnetic resonance - Cardoso, Josiane de O. [UNESP]; Silva, Bianca F. da [UNESP]; Venancio, Tiago; Rocha Pitta, Marina G. da; Pitta, Ivan da R.; Peccinini, Rosangela G. [UNESP]; Oliveira, Regina V. (Elsevier B.V., 2019)
A potent synthetic alpha(2)-adrenergic agonist called PT-31, (3-(2-chloro-6-fluorobenzyI)-imidazolidine-2,4-dione), was recently detected as a potential drug to be used as an adjuvant drug to treat chronic pain. The excellent pharmacological property of PT-31 highlights the importance in elucidating its metabolism, which could provide valuable information about its metabolite profile for further pharmacokinetics studies and additionally to estimate the impact of its metabolites on the efficacy, safety and elimination of PT-31. In this work, the study of the in vitro metabolism of PT-31 was initially carried out by using a liquid chromatography coupled to ion trap multiple-stage mass spectrometer (LC-IT-MSn) and a hybrid triple quadrupole/linear ion trap mass spectrometer (LC-QTrap). The production of at least three unknown oxidative metabolites was observed. Structural identification of the unknown metabolites was carried out by combination of LC-MS experiments, including selected reaction monitoring (SRM) and multi-stage full scan experiments. Further analysis of H-1-NMR led to the structural confirmation of the major metabolite. The results indicated that PT-31 was metabolized by a hydroxylation reaction in the imidazolidine-2,4-dione ring in rat and human liver microsomes, producing the metabolite 3-(2-chloro-6-fluorobenzyl)-5-hydroxyimidazolidine-2,4-dione in rat liver microsomes. A carbon hydroxylation onto the benzyl ring, produced two other minor metabolites of the PT-31 in rat liver microsomes. (C) 2019 Published by Elsevier B.V.
Keywords: In vitro metabolism; Liver microsome; Cytochrome P450; LC-MS; Metabolite identification; alpha(2)-Adrenergic agonist